2016
DOI: 10.15376/biores.11.3.6708-6726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pretreatment of Single and Mixed Lignocellulosic Substrates on Production of Endoglucanase by Bacillus aerius S5.2

Abstract: A mixed substrate (MS) comprising oil palm empty fruit bunch (EFB), oil palm frond (OPF), and rice husk (RH) was evaluated for endoglucanase production by Bacillus aerius S5.2. Effects of sulphuric acid, sodium hydroxide, N-methylmorpholine-N-oxide (NMMO), and hydrothermal pretreatments on endoglucanase production were investigated. Endoglucanase production by B. aerius on the untreated (0.677 U/mL) and pretreated MS (0.305 -0.630 U/mL) was generally similar, except that the acid (0.305 U/mL) and hydrothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previously, a variety of microorganisms belonging to the genera Bacillus, Geobacillus, Thermotoga, Caldibacillus, Acidothermus, Caldocellum, and Clostridium were reported to produce thermostable cellulases [2]. Furthermore, an enhanced endoglucanase production by Bacillus aerius S52 on mixed lignocellulosic substrates was attempted [20]. However, there exist no previous reports of thermophilic B. aerius producing the thermotolerant cellulase, as the majority were reported in B. licheniformis and B. subtilis [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a variety of microorganisms belonging to the genera Bacillus, Geobacillus, Thermotoga, Caldibacillus, Acidothermus, Caldocellum, and Clostridium were reported to produce thermostable cellulases [2]. Furthermore, an enhanced endoglucanase production by Bacillus aerius S52 on mixed lignocellulosic substrates was attempted [20]. However, there exist no previous reports of thermophilic B. aerius producing the thermotolerant cellulase, as the majority were reported in B. licheniformis and B. subtilis [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Higher amount of lignin in pretreated solids may be unfavourable for cellulase production in many microorganisms [30,31]. Oke et al [12] also reported lower endoglucanase production on hydrothermal pretreated combined substrates compared to the NaOH-treated one. Thus, NaOH was selected as the preferred pretreatment method for the rest of the study.…”
Section: Selection Of Suitable Pretreatment Methods For Scbmentioning
confidence: 99%
“…This observation agrees with some previous studies, which suggested that extremes of pretreatment severity could be detrimental to cellulase biosynthesis in different microorganisms. The study by Oke et al [12] found that substrates pretreated with harsher treatments had lower enzyme production than those with milder treatments. They attributed this to the degradation of amorphous regions in the substrates because of the severe pretreatments.…”
Section: Effect Of Pretreatment Severity On Cellulase Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the titers of the free cellulases are low due to adsorption of the produced cellulases over the biomass particles. Oke et al [21] have seen maximum endoglucanases synthesis by Bacillus aerius S5.2 using untreated lignocellulose.…”
Section: Optimization Of Process Parameters For Carboxymethyl Cellula...mentioning
confidence: 98%